Endowing AIE with Extraordinary Potential: A New Au(I)‐Containing AIEgen for Bimodal Bioimaging‐Guided Multimodal Synergistic Cancer Therapy. (5th October 2021) - Zhang, Jing; Zou, Hang; Gan, Shifeng; He, Benzhao; Huang, Jacob C.; Peng, Chen; Lam, Jacky W. Y.; Zheng, Lei; Tang, Ben Zhong
Abstract: The development of high‐performance theranostic platforms is always an intractable challenge in modern medicine research. Herein, new luminescent materials that possess the advantages of high sensitivity, high resolution, and deep tumor‐penetrating imaging as well as multimodal synergistic therapeutic functions may be one of the best potential alternatives for efficient theranostics. In this work, a powerful Au(I)‐containing aggregation‐induce emission luminogen (AIEgen) with integrated multifunctions of bimodal imaging and multimodal combination therapy is developed. This simple small‐molecule system can simultaneously realize high‐contrast fluorescence imaging and computed tomography imaging. Additionally, it can act as an effective thioredoxin reductase inhibitor to exert inherent anticancer effect, and simultaneously work as an ideal radiosensitizer to produce efficient anticancer efficacy through a multimodal synergistic effect. Thus, this study highlights a new design guideline to endow AIE luminogens with extraordinary functions by Au(I) and opens a new avenue for the development of new luminescent theranostic systems. Abstract : A unique small‐molecule aggregation‐induce emission luminogen (AIEgen) is developed and this simple molecule can achieve bimodual fluorescence and computed tomography imaging. Additionally, it not only can inhibit thioredoxin reductase activity to exert an anticancer effect, but also can work as an ideal radiosensitizer to boost the anticancer efficacy. Ultimately, the multimodal synergistic effects result in highly efficient anticancer efficacy.